Dux facilitates post-implantation development, but is not essential for zygotic genome activation. Issue 1 (30th September 2020) - Bosnakovski, Darko; Gearhart, Micah D; Ho Choi, Si; Kyba, Michael
Abstract: Double homeobox genes are unique to eutherian mammals. It has been proposed that the DUXC clade of the double homeobox gene family, which is present in multicopy long tandem arrays, plays an essential role in zygotic genome activation (ZGA). We generated a deletion of the tandem array encoding the DUXC gene of mouse, Double homeobox (Dux), and found it surprisingly to be homozygous viable and fertile. We characterize the embryonic development and ZGA profile of knockout (KO) embryos, finding that zygotic genome activation still occurs, with only modest alterations in 2-cell embryo gene expression, no defect in in vivo preimplantation development, but an increased likelihood of post-implantation developmental failure, leading to correspondingly smaller litter sizes in the KO strain. While all known 2-cell specific Dux target genes are still expressed in the KO, a subset is expressed at lower levels. These include numerous genes involved in methylation, blastocyst development, and trophectoderm/placental development. We propose that rather than driving ZGA, which is a process common throughout the animal kingdom, DUXC genes facilitate a process unique to eutherian mammals, namely the post-implantation development enabled by an invasive placenta. Abstract : Summary sentence: Mouse Dux is not absolutely required for viability or fertility, nor for zygotic genome activation, however the subset of Dux knockout embryos, post-implantation development fails.